2017
DOI: 10.1108/mabr-01-2017-0005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dry port implementation in Ghana

Abstract: Purpose Congestion at Ghana’s main seaports is a problem that has received much attention recently. This is as a result of continuous increase in containerized cargo. To increase the capacity of Ghana’ seaport, the Ministry of Transport through the Ghana Shippers Council initiated the Boankra Inland Port Project. The aim of this paper is to assess the feasibility and economic effects of implementing the Boankra Inland Port as a solution to reduce congestion at the main seaports, as well as reduce transportatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Location management 32 (Roso, 2008), (Rahimi et al, 2008), (Rosa and Roscelli, 2009), , , (Chang et al, 2011), (Flämig and Hesse, 2011), (Bentaleb et al, 2016a), , (Feng et al, 2013), (Rožić et al, 2014), (Ambrosino and Sciomachen, 2014), (Awad-Núñez et al, 2014), (Chang et al, 2015), (Awad-Núñez et al, 2015), (Roso et al, 2015a), (Awad-Núñez et al, 2016a), (Awad-Núñez et al, 2016b), (Muravev and Rakhmangulov, 2016), , (Wang et al, 2018), , (Monios and Wilmsmeier, 2012a), (Santos and Guedes Soares, 2017), (Raimbault, 2019), (Ližbetin, 2019), (Van Nguyen et al, 2019), (Chang et al, 2019a), (Gonzalez-Aregall andBergqvist, 2019), (Owusu Kwateng et al, 2017), (Black et al, 2018), (Sun and Wang, 2018), (Abdoulkarim et al, 2019b).…”
Section: Number Of Articles Articlesmentioning
confidence: 99%
“…Location management 32 (Roso, 2008), (Rahimi et al, 2008), (Rosa and Roscelli, 2009), , , (Chang et al, 2011), (Flämig and Hesse, 2011), (Bentaleb et al, 2016a), , (Feng et al, 2013), (Rožić et al, 2014), (Ambrosino and Sciomachen, 2014), (Awad-Núñez et al, 2014), (Chang et al, 2015), (Awad-Núñez et al, 2015), (Roso et al, 2015a), (Awad-Núñez et al, 2016a), (Awad-Núñez et al, 2016b), (Muravev and Rakhmangulov, 2016), , (Wang et al, 2018), , (Monios and Wilmsmeier, 2012a), (Santos and Guedes Soares, 2017), (Raimbault, 2019), (Ližbetin, 2019), (Van Nguyen et al, 2019), (Chang et al, 2019a), (Gonzalez-Aregall andBergqvist, 2019), (Owusu Kwateng et al, 2017), (Black et al, 2018), (Sun and Wang, 2018), (Abdoulkarim et al, 2019b).…”
Section: Number Of Articles Articlesmentioning
confidence: 99%
“…This, reflects the operation modes of ship chandlers' trucks. Moreover, there are many other reasons for truck congestions such as growing container volume, improper planning and time loss (Meersman et al, 2012b;Gidado, 2015;Cordero, 2014;Kwateng et al, 2017). However, the causative factors for port congestion vary in different ports.…”
Section: Port Congestionmentioning
confidence: 99%
“…For the environmental factor, previous studies found out that the activities of port and inland port operations had a significant environmental effect on the local people and the regions (van Duin and Van Der Heijden, 2021). It was highlighted that the development of inland ports could reduce the congestion and pollution issues caused by the seaport (Kwateng et al, 2017). Meanwhile, the congestion will increase carbon emissions and reduce air quality, thereby significantly increasing the mortality rate of drivers and affect the health of nearby residents (Zhang and Batterman, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%